2000
DOI: 10.1046/j.1365-2710.2000.00262.x
|View full text |Cite
|
Sign up to set email alerts
|

Comparative effectiveness of general practitioner versus pharmacist dosing of patients requiring anticoagulation in the community

Abstract: There is no apparent detriment to INR control when pharmacist management is compared with that of GPs. The overall proportion of INR estimations within the prescribed range is greater for pharmacists than for GPs and the interval between tests is longer for pharmacists compared with GPs.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
1

Year Published

2004
2004
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 13 publications
0
15
0
1
Order By: Relevance
“…The advantages of pharmacist‐led anticoagulation clinics, both in hospital outreach settings and in GP practices or primary care clinics are well established, but the same issues of patient convenience and accessibility still pertain . There are relatively few reported studies of services based at community pharmacies.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The advantages of pharmacist‐led anticoagulation clinics, both in hospital outreach settings and in GP practices or primary care clinics are well established, but the same issues of patient convenience and accessibility still pertain . There are relatively few reported studies of services based at community pharmacies.…”
Section: Discussionmentioning
confidence: 99%
“…Not surprisingly, there was a very strong preference for capillary over venous sampling, as was found previously in a study by Woods et al [27] The advantages of pharmacist-led anticoagulation clinics, both in hospital outreach settings and in GP practices or primary care clinics are well established, but the same issues of patient convenience and accessibility still pertain. [18][19][20][21][22] There are relatively few reported studies of services based at community pharmacies. The current study underlined the benefits reported in those studies, including greater convenience and accessibility for patients, a greater clinical role for community pharmacists and a reduced burden on general practice.…”
Section: Wider Contextmentioning
confidence: 99%
See 1 more Smart Citation
“…Because several studies have demonstrated that pharmacistand nurse-managed anticoagulation clinics perform as well or better than physician-managed usual care [18][19][20], pharmacists, nurses and other allied health care practitioners provide a significant proportion of all chronic anticoagulation management in the United States. Because several studies have demonstrated that pharmacistand nurse-managed anticoagulation clinics perform as well or better than physician-managed usual care [18][19][20], pharmacists, nurses and other allied health care practitioners provide a significant proportion of all chronic anticoagulation management in the United States.…”
Section: Discussionmentioning
confidence: 99%
“…Navedena farmaceutska usluga sprovodi se na sekundarnom/tercijarnom nivou zdravstvene zaštite, u tkzv. antikoagulantnim klinikama, od strane kliničkog farmaceuta u saradnji sa lekarom i drugim članovima zdravstvenog tima [7]. Ključni elementi ovog kompleksnog pristupa podrazumevaju: interpretaciju vrednosti INR-a; prilagođavanje doze varfarina (prema vodičima dobre kliničke prakse zasnovanim na dokazima); procenu i dokumentovanje rizika od krvarenja i tromboembolijskih događaja; upravljanje reverzijom prekomerne antikoagulacije; razmatranje promena u ishrani, primeni lekova i kliničkom stanju pacijenta (kao faktora koji bi mogli uticati na odnos doza-terapijski odgovor); edukaciju i savetovanje pacijenata; procenu stepena njihove adherence i razumevanja u vezi sa primenom antikoagulantne terapije, kao i zakazivanje termina naredne kontrole i merenja INR-a [3,8,9].…”
Section: Uvodunclassified